Stellar populations in local AGNs: evidence for enhanced star formation in the inner 100 pc. Issue 3 (24th November 2021) - Dahmer-Hahn, L G; Riffel, R; Rodríguez-Ardila, A; Riffel, R A; Storchi-Bergmann, T; Marinello, M; Davies, R I; Burtscher, L; Ruschel-Dutra, D; Rosario, D J
ABSTRACT: In modern models and simulations of galactic evolution, the star formation in massive galaxies is regulated by an ad hoc active galactic nuclei (AGN) feedback process. However, the physics and the extension of such effects on the star formation history of galaxies is matter of vivid debate. In order to shed some light in the AGN effects over the star formation, we analysed the inner 500 × 500 pc of a sample of 14 Seyfert galaxies using GMOS and MUSE integral field spectroscopy. We fitted the continuum spectra in order to derive stellar age, metallicity, velocity, and velocity dispersion maps in each source. After stacking our sample and averaging their properties, we found that the contribution of young SP, as well as that of AGN featureless continuum both peak at the nucleus. The fraction of intermediate-age SPs is smaller in the nucleus if compared to outer regions, and the contribution of old SPs vary very little within our field of view (FoV). We also found no variation of velocity dispersion or metallicity within our FoV. Lastly, we detected an increase in the dust reddening towards the center of the galaxies. These results lead us to conclude that AGN phenomenon is usually related to a recent star formation episode in the circumnuclear region.